2009
DOI: 10.5539/ijbm.v3n10p65
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Detection and Audit Expectation Gap: Empirical Evidence from Iranian Bankers

Abstract: Our focus in this study is to determine the expectation gap in auditor's responsibility between auditors and bankers in Iran. In the view of fact, the key factor in enhanced credibility is the perception of stakeholders that the external auditors judge to financial statements providing through the management. In recent years corporate scandals were happened, so third parties demand auditors should be as an honest judge. Third parties expect the auditors should have more responsibility to detect fraud. The audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 9 publications
1
20
0
3
Order By: Relevance
“…The accounting and auditing literature has consistently reported the existence of the AEG in both developed and developing countries (Alleyne and Howard, 2005;Barrett, 2010;Best et al, 2001;Dixon et al, 2006;Fadzly and Ahmad, 2004;Haniffa and Hudaib, 2007;Hassink et al, 2009;Lin, 2004;Lin and Chen, 2004;Onumah et al, 2009;PCAOB, 2011;Pourheydari and Abousaiedi, 2011;Salehi and Azary, 2009;Schneider and Church, 2008;Sidani, 2007). Despite efforts made to narrow the AEG, such as through enhancing the auditing standards and revising the format of the auditor's report, the AEG continues to exist, and in particular, the gap with regard to the auditor's responsibilities for fraud prevention and detection (Best et al, 2001;Dixon et al, 2006;Fadzly and Ahmad, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…The accounting and auditing literature has consistently reported the existence of the AEG in both developed and developing countries (Alleyne and Howard, 2005;Barrett, 2010;Best et al, 2001;Dixon et al, 2006;Fadzly and Ahmad, 2004;Haniffa and Hudaib, 2007;Hassink et al, 2009;Lin, 2004;Lin and Chen, 2004;Onumah et al, 2009;PCAOB, 2011;Pourheydari and Abousaiedi, 2011;Salehi and Azary, 2009;Schneider and Church, 2008;Sidani, 2007). Despite efforts made to narrow the AEG, such as through enhancing the auditing standards and revising the format of the auditor's report, the AEG continues to exist, and in particular, the gap with regard to the auditor's responsibilities for fraud prevention and detection (Best et al, 2001;Dixon et al, 2006;Fadzly and Ahmad, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…Bu zorluğa ilişkin önemli bir diğer husus da, denetçilerin hilenin tespit edilmesine ve engellenmesine yönelik düzenlemeleri uygulayabilmelerinin, işletmelerde sürekli olarak hazır bulunmalarını gerektirmesidir [4]. Diğer taraftan finansal tablo kullanıcılarının temel beklentisi denetlenen finansal tabloların hile içermeyecek şekilde değerlendirildiği, aksi takdirde bağımsız denetimin yararlı olmayacağı yönündedir [5]. Finansal tablo kullanıcılarının bağım-sız denetimden beklentileri ile denetçilerin denetime ilişkin sorumlulukları arasındaki bu görüş ayrılığı, "beklenti açığı" olarak ifade edilmektedir [5].…”
Section: Deneti̇mde Beklenti̇ Açiğiunclassified
“…Diğer taraftan finansal tablo kullanıcılarının temel beklentisi denetlenen finansal tabloların hile içermeyecek şekilde değerlendirildiği, aksi takdirde bağımsız denetimin yararlı olmayacağı yönündedir [5]. Finansal tablo kullanıcılarının bağım-sız denetimden beklentileri ile denetçilerin denetime ilişkin sorumlulukları arasındaki bu görüş ayrılığı, "beklenti açığı" olarak ifade edilmektedir [5]. Bu bağlamda denetçiler denetimin doğasından kaynaklanan zaman ve maliyet kısıtı nedeniyle hilenin tespit edilmesinin kendi sorumlulukları olmaması gerektiği görüşündedir [6].…”
Section: Deneti̇mde Beklenti̇ Açiğiunclassified
“…The results reveal that there is an expectation gap in several aspect of audit function in India. A survey conducted by Salehi and Azary (2008) regarding fraud detection in Iran between bankers and auditors. The result of study revealed that there was a gap between two parties on auditors' responsibility on fraud detection.…”
Section: Review Of Literaturementioning
confidence: 99%